Advances in identifying GM plants: current frame of the detection of transgenic GMOs - Bertheau, Yves (Burleigh Dodds Series in Agricultural Science, 2021)
Transgenic GMOs were welcomed in the 1990s due to the difficulties distinguishing genetic and epigenetic modifications from random mutagenesis and their ability to insert new nucleic sequences more rapidly but still randomly. Their marketing in Europe has been accompanied by health and environmental risk assessments, specific monitoring and traceability procedures to preserve the free choice of consumers and allow the coexistence of different supply chains. This chapter reviews the regulations, detection techniques, strategies and standards that have been put in place in the European Union since 1996 to ensure the analytical traceability of these GMOs. The capacity of the matrix approach, initially targeted at transgenic GMOs, to trace other types of GMOs is discussed in an accompanying chapter.